Sustainability Practices and Financial Performance in a High-Impact Industry: Evidence from Indonesian Chemical Firms - Annisa, Ghefira Nur; Saputri Mashuri, Ayunita Ajengtiyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Firms in Indonesia’s chemical sub-sector face growing expectations to strengthen sustainability initiatives without undermining financial performance. Nevertheless, prior studies report inconsistent results on whether Environmental, Social, and Governance (ESG) disclosure, green accounting adoption, and intellectual capital contribute to improved financial outcomes, particularly in emerging markets. This study examines the influence of ESG disclosure, green accounting practices, and intellectual capital on the financial performance of chemical sub-sector companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative approach, the study analyzes panel data covering the 2020–2023 period. A purposive sampling method yielded 18 firms that met the research criteria. Multiple linear regression was employed to test the proposed relationships, with STATA used for data processing and estimation. The results indicate that ESG disclosure, green accounting implementation, and intellectual capital do not significantly affect firms’ financial performance during the study period. These findings provide sector-specific evidence from Indonesia’s chemical industry and enrich the limited literature on the ESG–financial performance relationship in capital-intensive sectors within emerging-market